Activity Analysis An Approach to Improving the Evaluation Design of Ongoing Educational Programs - Iwanicki, Edward F. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
Problems are frequently encountered when attempting to improve the evaluation design of an ongoing educational program which has not made adequate provisions for evaluation. Usually the objectives of such a program are too global to guide the evaluator in the development of a more functional evaluation design. This paper presents a discussion of the activity analysis approach which is helpful in such a situation to obtain information needed in the development of an improved evaluation design. Once this information has been obtained it can be used by an evaluator in the development of a more comprehension evaluation design for the ongoing program. (Author)
ERIC Note: Paper presented at the Annual Meeting of the National Council on Measurement in Education (Chicago, Illinois, April, 1974).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Communication Problems; Consultants; Educational Programs; Evaluation Methods; Formative Evaluation; Objectives; Program Administration; Program Evaluation; Summative Evaluation; Speeches/Meeting Papers